Vibration Characteristics and Reduction Analysis of Lifting Pipe under Ocean Current. (5th July 2021) - Song, Qinghui; Jiang, Haiyan; Song, Qingjun; Xiao, Linjing; Zhong, PeiSi
Abstract : Effects of vibration absorbers on the lifting pipe in deep-sea mining have been attracting more and more attention in the recent three decades; however, there are very few reports about the influence of ocean current on the pipe vibration in the literature. Considering the geometrical features of the prototype, this paper establishes the physical model, mathematical model, and simulation model of the lifting subsystem. A comprehensive finite element model for the deep-sea mining system by the OrcaFlex is developed to explore the influences of buffer mass and sailing velocity on the deflection angle and the axial load and stress of the lifting pipe. Analytical and numerical simulations have been formulated to illustrate variation rule of longitudinal vibration and axial stress at the position of pump and buffer for the lifting subsystem to determine the dynamic vibration absorber parameters. In this paper, MATLAB and Orcaflex software are used to verify the mathematical model. The simulation results show that the attaching DVAs can effectively reduce the axial stress, and longitudinal displacement at certain positions of the lifting pipe.